Liver-specific activation of AMPK prevents steatosis on a high fructose diet - Carling,D; Woods,A; Williams,JR; Muckett,PJ; Mayer,FV; Liljevald,M; Bohlooly-Y,M (Cell Reports, 2017)
AMP-activated protein kinase (AMPK) plays a key role in integrating metabolic pathways in response to energy demand. We identified a mutation in the γ1 subunit (γ1D316A) that leads to activation of AMPK. We generated mice with this mutation to study the effect of chronic liver-specific activation of AMPK in vivo. Primary hepatocytes isolated from these mice have reduced gluconeogenesis and fatty acid synthesis, but there is no effect on fatty acid oxidation compared to cells from wild-type mice. Liver-specific activation of AMPK decreases lipogenesis in vivo and completely protects against hepatic steatosis when mice are fed a high-fructose diet. Our findings demonstrate that liver-specific activation of AMPK is sufficient to protect against hepatic triglyceride accumulation, a hallmark of non-alcoholic fatty liver disease (NAFLD). These results emphasize the clinical relevance of activating AMPK in the liver to combat NAFLD and potentially other associated complications (e.g., cirrhosis and hepatocellular carcinoma).